The Presence Project - Gaver, Bill (Practice as Research, 2020)
The influential Presence Project brought together an international group of collaborators in 2001 to investigate how technology can be used to increase the presence of older people in their local communities. This became a groundbreaking project for practice-based design research, exploring approaches and methods that have resonated since. The design team rejected a problem-solving approach, focusing instead on creating new and unusual situations for communication and insight. They introduced cutting-edge methods and developed challenging designs that they tested in the communities themselves. This book documents the Presence Project's development of key concepts in contemporary technology design, including cultural probes, design workbooks, and speculative design. Original Presence Project participants may have been surprised that the methods they invented became standard practice; the theme of the project was to break out of conventional approaches and try something radically new. With a new preface by Bill Gaver and an introduction by Phoebe Sengers, this reissue of The Presence Project gives readers a glimpse into the thinking behind this influential project and ideas about how to bring it to bear on today's design problems.